PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE DENGAN MEDIA FLASH CARD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKASISWA KELAS VIIA SMPN 3 SIKUR PADA MATERI POKOK PECAHAN TAHUN PELAJARAN 2016/2017 - Ulfa, Siti Maria; Sabrun, Sabrun; Agusfianuddin, Agusfianuddin (Media Pendidikan Matematika, 2018)
this study aims to describe the application of cooperative learning model picture and picture by using the media flashcard can improve student learning outcomes in mathematics class VIIA SMPN 3 Sikur the academic year 2016/2017 in the subject matter fractions. A common issue is the mathematics subjects are still considered abstract, and difficult. The use of the model and the use of media is less precise, less varied. Thus, the lack of attention that adversely affects the student learning outcomes. The use of appropriate methods and media are expected to improve learning outcomes. The use of the learning model type of picture and picture by using the media flashcard is one of the solutions offered to solve the problem. This research is a classroom action research (PTK) is conducted in two cycles. Types of data used are: Qualitative sheet teacher observation and student observation sheet, quantitative data obtained from the results of student evaluation tests given at the end of each cycle. The results showed that there was an increase in student learning outcomes, where the results of the first cycle with the classical percentage of 70% and the second cycle peresentase by 87%. Thus, it can be concluded that the application of cooperative learning model picture and picture by using the media flashcard can improve student learning outcomes class VIIA SMPN 3 Sikur in Academic Year 2016/2017.